Servo tracking of targets at sea - Ahmed, Anis; Brdyś, Mieczysław A. (Zielona Góra: Uniwersytet Zielonogórski)
This paper details a proposal for the position control system of a two-axis ship-mounted tracker. Aspects of the non-linear dynamics governing Line-Of-Sight (LOS) errors between the tracker and the target are presented. It is shown that the regulation of LOS errors can be achieved by introducing a feed-forward term based on the target's velocity. This velocity is not measurable, and an estimator is required.
Keywords: target tracking; tracker; Kalman filters; adaptive control